Social determinants of psychological wellness for children and adolescents in rural NSW - Peters, Ingrid (BMC Public Health, 2019)
BACKGROUND: The mental wellness of children and adolescents in rural Australia is under researched and key to understanding the long-term mental health outcomes for rural communities. This analysis used data from the Australian Rural Mental Health Study (ARMHS), particularly the parent report Strengths and Difficulties Questionnaire (SDQ) measure for children under 18 years old and their reporting parent’s demographic information to compare this sample’s mental wellness scores to the Australian norms and to identify what personal, family, community and rurality factors contribute to child mental wellness as pertaining to the SDQ total and subdomain scores. METHOD: Five hundred thirty-nine children from 294 families from rural NSW were included. SDQ scores for each child as well as personal factors (sex and age), family factors (employment status, household income and sense of community of responding parent), community SES (IRSAD) and rurality (ASCG) were examined. RESULTS: Children and adolescents from rural areas had poorer mental wellness when compared to a normative Australian sample. Further, personal and family factors were significant predictors of the psychological wellness of children and adolescents, while after controlling for other factors, community SES and level of rurality did not contribute significantly. CONCLUSIONS: Early intervention for children and families living in rural and remote communities is warranted particularly for low income families. There is a growing need for affordable, universal and accessible services provided in a timely way to balance the discrepancy of mental wellness scores between rural and urban communities.